The effect of the impact of customer satisfaction on retail layout: Perspective of PT Trans Retail Medan Carrefour - Dilla Syadzwina; Nelly Artha Naibaho; Yolanda Br.Sihaloho; Putri Dwi Jelita Waruwu; Ivo Selvia Agusti (International Journal of Economics, Commerce, and Management, 2025)
This study aims to analyze the effect of retail layout on customer satisfaction levels at PT Trans Retail Medan Carrefour. In an increasingly competitive retail industry, store layout is one of the strategic factors that can affect comfort, shopping efficiency, and customer perceptions of service quality. This study uses a quantitative approach with descriptive and associative methods, involving 60 respondents who are active customers of Transmart Carrefour Medan. Data collection techniques were carried out through distributing questionnaires and direct observation. The results of multiple linear regression analysis show that retail layout has a significant effect on customer satisfaction, with a contribution of 75.9% to the variation in satisfaction levels. The layout factors that contribute the most include product placement, aisle design, lighting, signage, and ease of access between areas. These findings emphasize the importance of optimizing store layout as a strategy to improve the shopping experience and customer loyalty. Thus, retail management is advised to continue to evaluate and innovate in spatial planning in order to meet consumer expectations sustainably.